1988
DOI: 10.1007/bf00922768
|View full text |Cite
|
Sign up to set email alerts
|

Firearm violence and the effects of gun control legislation

Abstract: Two gun control laws designed to reduce different types of violent crimes were evaluated. In 1981, East St. Louis, IL, imposed stricter penalties for individuals who carry firearms outside their homes for protection (individuals could keep firearms in their homes). This law had only a temporary impact in reducing firearm use in assaults and robberies. In Evanston, IL, a slightly different approach was taken with legislation that banned handguns in the entire city (i.e., individuals could not keep handguns with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Much like the comparative literature, U.S.-based research on firearm availability and crime has demonstrated a similar degree of inconsistency, which may also be attributed to methodological limitations. Specifically, several studies have pointed to reductions in violence with increased firearm restrictions (Koper and Roth 2001a; Kwon and Baack 2005; Loftin et al 1991; McDowall et al 1996; Zimring 1972; Zimring and Hawkins 1997), while others have reported either a null (Black and Nagin 1998; Britt et al 1996; Jung and Jason 1988; Kleck and Patterson 1993) or a negative relationship (Kleck 2001, 2015; Kleck and McElrath 1991; Lott and Mustard 1997). As with the comparative scholarship, these differences could be due to data limitations resulting in the omission of potentially important confounders (Britt et al 1996; Kleck 2001) or difficulties in isolating the causal influence of policy given the distinctions between the official effective date and when the first violators are sentenced (Britt et al 1996; Jung and Jason 1988; Kwon and Baack 2005).…”
Section: Firearm-crime Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Much like the comparative literature, U.S.-based research on firearm availability and crime has demonstrated a similar degree of inconsistency, which may also be attributed to methodological limitations. Specifically, several studies have pointed to reductions in violence with increased firearm restrictions (Koper and Roth 2001a; Kwon and Baack 2005; Loftin et al 1991; McDowall et al 1996; Zimring 1972; Zimring and Hawkins 1997), while others have reported either a null (Black and Nagin 1998; Britt et al 1996; Jung and Jason 1988; Kleck and Patterson 1993) or a negative relationship (Kleck 2001, 2015; Kleck and McElrath 1991; Lott and Mustard 1997). As with the comparative scholarship, these differences could be due to data limitations resulting in the omission of potentially important confounders (Britt et al 1996; Kleck 2001) or difficulties in isolating the causal influence of policy given the distinctions between the official effective date and when the first violators are sentenced (Britt et al 1996; Jung and Jason 1988; Kwon and Baack 2005).…”
Section: Firearm-crime Researchmentioning
confidence: 99%
“…Specifically, several studies have pointed to reductions in violence with increased firearm restrictions (Koper and Roth 2001a; Kwon and Baack 2005; Loftin et al 1991; McDowall et al 1996; Zimring 1972; Zimring and Hawkins 1997), while others have reported either a null (Black and Nagin 1998; Britt et al 1996; Jung and Jason 1988; Kleck and Patterson 1993) or a negative relationship (Kleck 2001, 2015; Kleck and McElrath 1991; Lott and Mustard 1997). As with the comparative scholarship, these differences could be due to data limitations resulting in the omission of potentially important confounders (Britt et al 1996; Kleck 2001) or difficulties in isolating the causal influence of policy given the distinctions between the official effective date and when the first violators are sentenced (Britt et al 1996; Jung and Jason 1988; Kwon and Baack 2005). As with international studies, causal ordering and simultaneity bias are potential concerns in terms of the likely two-way relationship between firearm availability and crime rates (Hauser and Kleck 2013; Kleck et al 2011; Kleck and Patterson 1993).…”
Section: Firearm-crime Researchmentioning
confidence: 99%
“…Study r s k Braga, Kennedy, Waring, & Piehl (2001) -.412 .126 9 Britt, Kleck, & Bordura (1996) -.149 .149 8 Cohen & Ludwig (2003) -.416 .201 4 Jung & Jason (1988) .240 .235 4 Kleck & Patterson (1993) -.026 .074 9 Koper & Roth (2001) -.037 -1 Kwon, Scott, Safranski, & Bae (1997) -.242 .068 2 Lester & Murrell (1986) -.005 .106 2 Loftin, Heumann, & McDowall (1983) -.101 .097 9 Loftin & McDowall (1984) -.105 .177 3 Lott & Whitley (1999) .029 .070 5 Ludwig & Cook (2000) .002…”
Section: Appendixmentioning
confidence: 99%
“…Another study (McDowall, Lizotte, and Wiersema, 1991) reports no change in assault rates, but a significant decrease in the number of reported burglaries, as a result of these laws. A fourth study (Jung and Jason, 1988) found that firearm assaults decreased significantly in the days before new regulations went into effect but showed no change after the law became effective. The results of that study were attributed to intensive media coverage of the new law prior to enactment.…”
Section: Policy Change Interventionsmentioning
confidence: 99%